STUDI TENTANG KOMPETENSI PEDAGOGIK DAN PROFESIONAL BAGI GURU GEOGRAFI DI SMA NEGERI KABUPATEN PATI - Suharini, Erni (Jurnal Geografi, 2014)
The teacher has a very strategic role in efforts to achieve national developmentgoals, particularly in education field, so it is necessary to develop asprofessionals whoâs dignified and professional. Recognizing these conditions, thegovernment made efforts to develop competency standards. Under theseconditions, the researchers want to examine: (1) What condition of GeographyTeacher pedagogical competence in SMA Pati; (2) How does the professionalcompetence of geography teachers in SMA Pati. The population in this study wasa geography teacher at SMA Pati. Methods of data collection weredocumentation, observation, and interviews. Variables research is pedagogicalcompetence and professional competence for geography teachers in SMA Pati.The data obtained were processed using descriptive methods and statisticalanalysis with the percentage of Mann-Whitney test. The results of this studyindicate that geography teachers have pedagogical competence of 68.8%included in both criteria. But there was an indicator that included in the criteriawas not good, i.e. the evaluation tool accuracy. This is due to the lack ofteacherâs competences in providing feedback and assessment during the learningprocess. While on the professional competence of geography teachers are ownedby 70.5% included in both criteria.